Cellular strategies for controlling protein aggregation - Tyedmers, Jens; Mogk, Axel; Bukau, Bernd (Nature reviews, 2010)
Cellular systems for protein quality control act to refold or degrade misfolded proteins, thereby preventing protein aggregation. Stress conditions and ageing can lead to an exhaustion of this protective system, causing the generation of protein aggregates.The structures of protein aggregates are highly variable, ranging from amorphous to highly ordered amyloid fibrils, all of them sharing an increased β-sheet content.Cells control protein aggregation by directing misfolded proteins to distinct deposition sites.Protein aggregates are frequently segregated in an asymmetric manner during cell division, allowing the generation of damage-free daughter cells.Cells have developed different strategies to remove protein aggregates. The refolding of aggregated proteins in bacteria, yeast and plants is mediated by the cooperation of 70-kDa heat shock protein 70 (Hsp70) and Hsp104 chaperones and is facilitated by the co-aggregating of small HSPs. Aggregates can also be removed by autophagy, which is a major clearance pathway for aggregates in mammals.